Multicentre case–control study of pneumococcal infections among children with pneumonia in Peninsular Malaysia (MY-Pneumo): a study protocol - Ramzi, Nurul Hanis; Hoong, Andrew Tan Chun; Johari, Nur Alia; Nathan, Anna Marie; Teh, Cindy Shuan Ju; Sulaiman, Norhayati Aida; Ilias, Mohamad Ikram; Deris, Zakuan Zainy; Hazlan, Siti Nur Haidar; Mohamad Nasir, Nur Syafiqah; Abu Bakar, Asrar; Muhd Helmi, Muhd Alwi; et al. (Springer Nature, 2024)
Background S. pneumoniae (SPN) is the most common cause of pneumonia. The disease can be effectively prevented through immunisation. Since December 2020, the Malaysian Government has included the 10-valent pneumococcal conjugate vaccine (PCV10) for all infants born on or after 1 January 2020 as part of the National Immunisation Programme (NIP). However, the epidemiology of pneumonia remains poorly understood. To fill the knowledge gap, we established a multicentre surveillance study to understand the burden of pneumococcal pneumonia among young children in Peninsular Malaysia.